Transnational intergenerational relationships and doing transcultural family through mandarin learning: an ethnographic glance at Chinese dynamics in four intercultural families in Germany - Li-Gottwald, Jiayin (Frontiers in Sociology, 2024)
This article explores the micro dimension within the field of intercultural family studies. The ethnographic study focuses on Chinese elements in transcultural upbringing practices within families with Chinese mothers and German fathers raising their children in Germany. It builds on the notion of family figuration practice in transnational grandparents-grandchildren relations, particularly Confucian-based transnational grandparenting, and the development of a ‘third space’ for transcultural family upbringing within intercultural families. Additionally, it incorporates the concepts of discourse perspective of culture and assemblage to explore how Chinese culture and identity converge in a transcultural family upbringing context. The findings show that families have varied experiences with transnational intergenerational communication influenced by their life stage, language abilities, and socio-economic factors.